Gambaran Pengetahuan Bidan dan Perawat Tentang VKDB di Puskesmas Prabumulih Sumatera Selatan - Sri Utami; Muhamad Yunus; Deviani Utami (Puslitbang Sinergis Asa Professional, 2021)
Intracranial hemorrhage is a dangerous bleeding in infants. The impact of intracranial bleeding is in the form of death and sequelae, such as hydrocephalus, cerebral atrophy, encephalopathy, and epilepsy which will interfere with growth and development. One of the causes of intracranial bleeding is bleeding due to Vitamin K deficiency (VKDB). Meanwhile, intracranial bleeding due to vitamin K deficiency can be prevented by giving vitamin K1 to newborns. This study aimed to know the description of the level of knowledge of health workers about spontaneous intracranial bleeding caused by vitamin K deficiency bleeding at the Prabumulih Health Center, South Sumatra in 2020. The type of research used in this research is descriptive with a cross sectional design. The samples used in this study were nurses and midwives who worked at the Prabumulih Health Center in South Sumatra who had met the criteria in this study. The result showed that the frequency of sufficient knowledge of respondents was found as many as 31 people with a percentage of 46.3%. In conclusion Midwives at the Prabumulih health center in South Sumatra have a sufficient level of knowledge about intracranial bleeding due to vitamin K deficiency. It is hoped that this study can provide information to the public about the knowledge of intracranial bleeding due to vitamin K deficiency, so that the incidence of intracranial bleeding due to vitamin K deficiency and infant mortality can be reduced.